No mark upon her - Crombie, Deborah (New York : William Morrow & Co., 2012)
This mystery novel embroils Kincaid and James in the case of the puzzling drowning of a rower, a Met detective, on the Thames. It is twisting tale of psychological suspense, a story rich in deadly secrets, salacious lies, and unexpected betrayals. When an Olympic rowing hopeful and a detective with the Met is found dead in the Thames, Scotland Yard Superintendent Duncan Kincaid, along with his wife and his team, is submerged in a complex case involving political and ethical issues that put both his career and reputation on the line.
Map on endpapers.
A Kincaid and James detective mystery.
Keywords: Kincaid, Duncan -- (Fictitious character) -- Fiction; James, Gemma -- (Fictitious character from Crombie) -- Fiction; Police -- England -- London -- Fiction; Missing persons -- Fiction; Murder -- Investigation -- Fiction; London (England) -- Fiction; Mystery fiction; Psychological fiction